Pengembangan Animasi 2 Dimensi mengenai Pengenalan Pendidikan Seksual Berbasis Website Dipensa - Hannisa Safira Wafiana; Ahmad Samawi; Rosyi Damayani Twinsari Maningtyas (Comit: Communication, Information and Technology Journal, 2025)
Sex education is necessary for children because it will be used as protection against unwanted outcomes.Therefore, it is important to teach children about sex, especially sex education for young children. This research aims to create web-based sexual education for children that can be used in educational activities. This type of research is a Research & Development (R&D) study, using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this research are students from group A. Meanwhile, the data collection instruments for this research are interviews, questionnaires, and documentation. The trial results show that 83% of content experts and 87% of media experts assess the effectiveness, efficiency, and appeal of the DIPENSA website. The validation results from material experts and media experts indicate that this website-based sexual education learning media meets the criteria of being very valid and can be used without revision. The trial results show that students better understand sexual education through the DIPENSA website after it was provided. Furthermore, based on field trials, the research results are categorized as fairly valid and usable, although some minor adjustments are needed.